Integrating Sharia Accounting and Green Finance to Strengthen Environmental Governance: A Triple Bottom Line Approach - Mareta Putri; Inten Meutia; Shelly Febriana Kartasari (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study explores the integration of Sharia accounting and green finance as a strategic framework to strengthen environmental governance through the Triple Bottom Line (TBL) approach People, Planet, and Profit. Using an exploratory and conceptual analysis method, this research examines how Islamic accounting principles emphasizing fairness, transparency, and moral responsibility align with green finance objectives centered on ecological and social sustainability. The findings reveal that Sharia-based financial instruments, such as green sukuk, play a crucial role in financing environmentally friendly projects without violating Islamic law. The integration enhances accountability, supports the achievement of Sustainable Development Goals (SDGs), and promotes ethical investment practices. However, implementation challenges remain, including regulatory inconsistency, limited stakeholder awareness, and the lack of standardized frameworks. The study recommends strengthening policy frameworks, improving green finance literacy, and fostering cross-sector collaboration. Overall, the synergy between Sharia accounting and green finance offers a holistic and ethical foundation for achieving sustainable economic, social, and environmental development in Indonesia.